Acculturation stress and psychological well-being in Latin American immigrant schoolchildren in a district of Santiago de Chile - Segovia-Lagos, Pablo (2023)
This study evaluated acculturation stress and psychological well-being in Latin American schoolchildren in a public school in Santiago de Chile. An acculturative stress scale and a psychological well-being scale were applied to 124 students between 8 and 15 years old (M = 13.09; DS = 1.52). The results indicate that the dimensions of the Acculturation Stress scale that report alteration are Longing with the country of origin and Adaptation to school, family and peers. In turn, psychological well-being is altered by the Positive Relationships and Domain of the environment dimensions. The most affected population are mainly men and that immigrant population that has been residing in the country for less than 6 months. This could be explained by the sociocultural differences between the country of origin and the host country and outgroup differences. It is concluded that stress due to acculturation and psychological well-being is influenced by the emotional distance that children and young people experience from their country of origin and adaptation to the new culture. Given that the school context is the gateway to the new culture, it is essential to emphasize its socializing role, where inclusion can allow building a common culture.